mTOR Inhibitor Use Is Associated With a Favorable Outcome of COVID-19 in Patients of Kidney Transplant: Results of a Retrospective Study - Pinchera, Biagio; Spirito, Lorenzo; Buonomo, Antonio Riccardo; Foggia, Maria; Carrano, Rosa; Salemi, Fabrizio; Schettino, Elisa; Papa, Fortuna; La Rocca, Roberto; Crocetto, Felice; Napolitano, Luigi; Villari, Riccardo; et al. (Frontiers in Medicine, 2022)
Introduction COVID-19 in solid organ transplant recipients is associated with a poor prognosis because of immunosuppression. Some studies suggest a potential therapeutic role of mTOR inhibitors in SARS-CoV-2 infection. This study aims to assess the impact of mTOR employment on the evolution and outcome of SARS-CoV-2 infection in solid organ transplant recipients. Methods We enrolled kidney transplant patients attending the A.O.U. Federico II of Naples and followed up from March 2020 to June 2021. On these, we evaluated the risk of acquiring SARS-CoV-2 infection, the clinical presentation of the disease, and its outcome together with the type of immunosuppressive therapy. Finally, we assessed the impact of m-TOR inhibitors on relevant clinical metrics of SARS-CoV-2 infection. Results We enrolled 371 patients. Of these, 56 (15.1%) contracted SARS-CoV-2 infection during the period of the study. No differences were observed among the different immunosuppressive therapies concerning the risk of acquiring SARS-CoV-2 infection. In contrast, the type of immunosuppressive therapy had a significant impact on the outcome of the disease. In details, patients who received mTOR inhibitors as part of their immunosuppressive therapy compared to other regimens had a lower chance of developing a moderate or severe disease (OR: 0.8, 95 CI (0.21-0.92); p: 0.041). Conclusion In patients receiving solid organ transplantation, the use of mTOR inhibitors as part of immunosuppressive regimen is associated with a better prognosis in case of COVID-19.